Coronavirus Related Mortality in the Geriatrics Ambulatory Practice. (June 2021) - George, Claudene J.; Guo, Alice
Background: Older adults often have atypical presentations of common diseases and COVID-19 is no exception. Presentations range from asymptomatic to overwhelming symptoms that result in hospitalization, intubation, or death. The number of COVID-19 related deaths among older adults in the outpatient practice during the peak of the pandemic is unclear. Methods: The objective is to describe the COVID-19 status and clinical characteristics of patients in a Geriatrics Ambulatory Practice who died during the peak of the COVID-19 pandemic. Design: Retrospective chart review Participants: 54 adults age 65 years and older. Methods: COVID-19 status defined by positive test result and presumed COVID-19 status based upon clinical presentation. Results: Out of 1200 active patients in the Geriatrics Ambulatory Practice, 54 (4.5%) died between January 1st, 2020 and June 30th, 2020. The study sample was 63% female, 33% Hispanic/Latino, 27% Black/African American, and 22% white. The mean (SD) age was 86(8.6) years, range (72-107 years). The most prevalent medical comorbidities in decreasing order of frequency were hypertension (88.9%), diabetes (51.9%), and cognitive impairment (51.9%). Nineteen (35%) were COVID-19 positive and 8 had presumed COVID-19. There were no statistically significant differences in age, gender, race/ethnicity, and medical comorbidities between the COVID-19 or presumed COVID-19 group compared to those with No COVID-19. Conclusion: Approximately 35% of Geriatric patients who died during the first 6 months of 2020 had confirmed COVID-19 and an additional 15% had presumed COVID-19. The actual number of COVID-19 related deaths among older adults in the ambulatory practice during the peak of the pandemic is difficult to estimate and likely underestimated.